Clinicopathological profile of malaria patients in an Central African United Nations hospital - Kohli, Kinshuk; Das, Amit K. (International Journal of Research in Medical Sciences, 2018)
Background: Malaria is one of the most widespread diseases in the world. It is endemic in 91 countries. Each year 300-500 million cases of malaria are confirmed with 1.5-2.7 million deaths. Malaria is a major public health problem in Africa. A large number of united nations troops are deployed in central Africa making them vulnerable to malaria infection. Present study was undertaken to find out the clinical and laboratory findings of malaria cases in a United Nation’s referral hospital in Central Africa. Methods: It is a retrospective study of 150 confirmed and treated cases of malaria for a period of one year in a referral hospital for peace keeping troops and employees of United Nations in Democratic Republic of Congo (DRC). Patients positive by ICT or slide positive were included. Detailed history, examination and lab features of these patients were recorded and analyzed. Results: A total of 150 patients were included in the study. Out of which 145 patients were of pure P. falciparum malaria, 02 patients had only P. vivax, and 03 patients were having mixed malaria. Fever was the main symptoms found in all patients. Headache was the second most predominant symptoms in (70%) patients. Other signs and symptoms were vomiting (31%), myalgia (38%), jaundice (10%), hepatosplenomegaly (15%), pallor (42%) and decreased urine output (8%). Duration of symptoms was between 4 to 15 days. Thrombocytopenia was observed in 43% patients. Jaundice in (10%), transaminitis in (25%). Anaemia was seen in 53% patients. Conclusions: Malaria was found to be the most common cause of admission in our hospital. It is important to suspect malaria in all persons deployed in DRC and presenting with fever and associated headache, jaundice, transaminitis and thrombocytopenia. Early diagnosis and treatment can be lifesaving to prevent complications and mortality.